COMMUNICATION PATTERNS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN BUILDING STUDENT RELIGIOSITY: FRAMING ANALYSIS - Utomo, Imam Aris; Nabila, Salma; Annafi’ah, Azizah Harda; Wahyuni, Sri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study investigates how Islamic Religious Education (PAI) teachers at MAN 2 Karanganyar construct and deliver religious messages through communication strategies that play a role in shaping students’ religiosity. This research is based on the need for teacher communication that not only focuses on delivering material but also functions as a medium for moral and spiritual development. Using a qualitative case study research design, data were collected through in-depth interviews, participatory observations, and documentation, and were analyzed using Entman’s framing model which includes problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings show that PAI teachers apply persuasive, dialogic, and contextual communication patterns combined with humor, role-modeling, and relevant examples that help students relate Islamic teachings to daily life. The framing of religious messages emphasizes moral discipline, worship obligations, and the relevance of Islamic values in contemporary contexts, which contributes to increased motivation, moral awareness, and student participation in religious activities. Overall, the study concludes that success in fostering religiosity in the madrasa is greatly influenced by the teacher’s ability to frame religious messages in a humanistic and meaningful manner according to the students’ life context. ABSTRAK Penelitian ini menginvestigasi bagaimana guru Pendidikan Agama Islam (PAI) di MAN 2 Karanganyar membangun dan menyampaikan pesan keagamaan melalui strategi komunikasi yang berperan dalam membentuk religiositas peserta didik. Penelitian ini berangkat dari kebutuhan akan komunikasi guru yang tidak hanya berfokus pada penyampaian materi, tetapi juga berfungsi sebagai medium pengembangan moral dan spiritual. Dengan menggunakan desain penelitian kualitatif studi kasus, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi, serta dianalisis menggunakan model framing Entman yang mencakup pendefinisian masalah, interpretasi kausal, evaluasi moral, dan rekomendasi penanganan. Temuan penelitian menunjukkan bahwa guru PAI menerapkan pola komunikasi persuasif, dialogis, dan kontekstual yang dipadukan dengan humor, keteladanan, dan contoh yang relevan sehingga membantu peserta didik mengaitkan ajaran Islam dengan kehidupan sehari-hari. Framing pesan keagamaan menekankan kedisiplinan moral, kewajiban ibadah, dan relevansi nilai-nilai Islam dalam konteks kontemporer, yang berkontribusi pada meningkatnya motivasi, kesadaran moral, dan partisipasi siswa dalam kegiatan keagamaan. Secara keseluruhan, penelitian ini menyimpulkan bahwa keberhasilan dalam menumbuhkan religiositas di madrasah sangat dipengaruhi oleh kemampuan guru membingkai pesan keagamaan secara humanis dan bermakna sesuai konteks kehidupan peserta didik.